Efficacy of a rational algorithm to assess allergy risk in patients receiving the BNT162b2 vaccine. Issue 44 (22nd October 2021) - Yacoub, Mona-Rita; Cucca, Valentina; Asperti, Chiara; Ramirez, Giuseppe A.; Della-Torre, Emanuel; Moro, Matteo; Zandalasini, Camilla; Di Napoli, Davide; Ambrosio, Alberto; Signorelli, Carlo; Colombo, Sergio; Beretta, Luigi; et al.
Highlights: Allergy to vaccines is rare but has a heavy impact amidst mass vaccination campaigns. History-based patient triaging helps mitigating allergy risk. BNT162b2 vaccine can safely be administered to high-risk allergic subjects. Abstract: Among 6146 hospital employees, 118 subjects with severe allergic background were identified through a screening questionnaire and stratified into 3 groups (Low-risk (LR), Intermediate (IR) and High-risk (HR) group), based on their allergic anamnesis. Data reports on hypersensitivity reactions (HypR) have been collected in both allergic and non-allergic subjects. Seventeen patients (14%) in the allergic population had a HypR after the first, the second or both doses. Skin manifestations were the most frequent ones. Allergic events were more frequent in HR (35%) than IR (10%; p = 0.005) or LR (0%; p = 0.074) subjects. No patient had anaphylaxis. All patients completed the vaccination schedule. 13 HypR occurred in patients without severe allergic background (13/6028, 0, 2%) including one (1/6148, 0.016% of total population) WAO grade-4 anaphylaxis. Our data suggest that BNT162b2 mRNA Covid-19 vaccine is relatively safe also in patients with severe allergic background; however, some precautions are required for high-risk patients.